KEMANDIRIAN EKONOMI KELUARGA BERBASIS RELIGIUSITAS: STUDI IMPLEMENTASI KAMPUNG TILAWAH KECAMATAN SILO KABUPATEN JEMBER - Warga Baroka Sugiarto,; Muhammad Korib Hamdani,; Sofiah, Sofiah (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the implementation of religious-based family economic development in Tilawah Village, Silo District, Jember Regency. Tilawah Village is known as a community that integrates religious values in community economic empowerment through various programs such as entrepreneurship training, women's empowerment and thematic religious studies. A qualitative approach was used in this study with data collected through interviews, observations, and documentation. The results of the study indicate that entrepreneur training contributes to improving community skills in utilizing local resources productively in accordance with the concept of family production functions. Women's empowerment programs increase women's roles in supporting the family economy without forgetting their primary responsibilities in the family. Meanwhile, thematic religious studies are an effective means of instilling Islamic business ethics values, such as honesty, blessings and social responsibility. This approach not only increases family economic independence, but also forms economic behavior based on religious values. These findings strengthen the theory of family economics that is oriented towards a balance between material and spiritual aspects.